Makna Modus Kondisional dalam Novel Histoire d’un Casse-Noisette karya Alexandre Dumas - Chrisvanya Yane, Wehell; Widyastuti, Wahyu; Ratna (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2025)
This study aims to identify the meaning of the conditional mood in the novel Histoire d’un Casse-Noisette by Alexandre Dumas. The main theory used is the theory of meaning of the conditional mood according to Boulares & Frérot (2019) and Michèle Mahéo-Le Coadic (2022). The method utilized in this study is content analysis, with data collection technique in form of documentation were used to collect data consisting words, phrases, and sentences in conditional form. based on the theory proposed by Sugiyono (2013). The data sources consist of a primary source which is novel “Histoire d’un Casse-Noisette” by Alexandre Dumas, and secondary sources including French grammar books, articles, and relevant journals discussing the conditional mood. The collected data were analysed with Miles and Huberman’s content analysis method according to Purrohman (2018) through three stages: data reduction, data presentation, and conclusion drawing. The data analysis shows 30 conditional sentences that can be categorized based on the theory used, which includes 9 sentences about uncertainty, 8 about desire, 5 about current impossibility, 4 about politeness, 1 about imagination, 1 about suggestion, 1 about reprimand, and 1 about past impossibility. From this research, it can be concluded that the conditional mood in the novel Histoire d’un Casse-Noisette by Alexandre Dumas reflects various meanings within the narrative and interactions among characters.